A century of stream burial in Michigan (USA) cities. Issue 1 (4th November 2016) - Napieralski, Jacob A.; Welsh, Eric S.
ABSTRACT: Following rapid expansion of urbanization over the last century, Michigan's largest cities are characterized by relatively high population densities, high percentages of impervious surface coverage, and heavily modified stream networks (e.g. channelization, dams, or burial). Unfortunately, urban stream burial can be extensive and costly, but the spatiotemporal pattern of stream burial in most cities remains ambiguous and, for the most part, unmapped. This map illustrates the impact of stream removal in Michigan's seven largest cities, both before and after rapid population growth and industrialization. Flowlines indicating the location of streams, artificial channels, and canals/ditches were accessed from the United States Geological Survey (USGS) National Hydrography Dataset (NHD) and digitized off historical USGS topographic maps between 1902 and 1929, ranging in scale between 1:62, 500 and 1:24, 000. A comparison between the two datasets showed all seven cities have stream networks altered or lost entirely to the practice of stream burial and removal. The City of Detroit has lost at least 85% of the stream channels since 1902, while other cities, such as Ann Arbor and Warren, have lost more than 60% of the stream network.